METODE SYARAḤ AL-SUYŪṬĪ DALAM AL-DĪBĀJ: Kritik terhadap Syaraḥ Hadis Penafsiran Surah al-Mā’idah Ayat 3 dan Perbandingannya dengan Syaraḥ al-Nawawī - Asrar Mabrur Faza (Jurnal Living Hadis, 2016)
This article studies about syaraḥ hadith method used by al-Suyūṭī in his al-Dībāj where he had developed eight forms of syaraḥ within this kitab, those are Ḍabṭ  al-alfāẓ, tafsīr al-garīb, bayān ikhtilāf riwāyāt alā al-qillah, ziyādah fī khabr lam tarid lahu ṭarīquhu, tasmīyah al-mubham, i‘rāb al-musykil, jam‘u baina al-mukhtalaf, as well īḍāh mubham. This study entails when Al-Suyūṭī applied those eight forms of syaraḥ in tafsir surah al-Mā’idah ayat 3 was paradoxically inconsistent. He modestly used tafsīr al-garīb and bayān  ikhtilāf  riwāyāt alā al-qillah, while at the same time benefited linguistic, normative-theology, historicity as approach as well as respected a syaraḥ writing method called qauluhu. In order to equivocate from plagiarizing al-Minhāj, this paper views that al-Suyūṭī intentionally had furthered his work with ijmālī method. This is how he judiciously amazed his reader.